Case Report: COVID-19 Presenting as Acute Undifferentiated Febrile Illness—A Tropical World Threat - Nunthavichitra, Surat (Am J Trop Med Hyg, 2020)
We report a young Thai man from the Thai-Myanmar border suffering from 2 days of fever and myalgia without respiratory tract signs or symptoms. He reported no history of travel through an area with confirmed COVID-19 cases or contact with sick persons. After excluding malaria and dengue, which are common causative agents of acute undifferentiated febrile illness (AUFI) in Thailand, chest radiography was performed according to the patient triage protocol of our institute for AUFI during the COVID-19 outbreak. Chest radiography revealed findings compatible with pneumonia. Nasopharyngeal, throat, and sputum samples tested positive for SARS-CoV-2 by real-time reverse transcriptase–PCR. The preadmission diagnosis of COVID-19 in this patient enabled appropriate management and isolation to prevent nosocomial transmission. Fever and nonspecific symptoms and laboratory results in early COVID-19 may be difficult to distinguish from tropical infectious diseases, especially when respiratory signs and symptoms are absent. This fact necessitates vigilant awareness in clinical investigation, management, and infection control, especially in tropical resource-limited settings.